2018
DOI: 10.4012/dmj.2017-373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the flexural mechanical properties of various thermoplastic denture base polymers

Abstract: This study evaluated the flexural mechanical properties of various thermoplastic denture base polymers (six polyamides, four acrylic resins, polyester, polypropylene, and polycarbonate) by three different testing conditions; specimens were tested in water bath at 37°C (Wet/Water, by ISO 20795-1), or in ambient air (Wet/Air) after being immersed in distilled water for 50 h, or after desiccation for 7 days (Dry/Air). The mean ultimate flexural strength (UFS) and flexural modulus (FM) for most products ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
3
18
0
2
Order By: Relevance
“…Specimens in the CNF-NB-A (0.05, 0.10, and 0.20 wt%) and CNF-NB-B (0.05 and 0.10 wt%) groups showed a significantly negative effect on flexural strength after immersion when compared with those in the other groups. This finding is consistent with the results of previous studies by Lee et al, where water or humid environment was reported to reduce the physical properties of some polymer resins 28,32) . The observation may be partially explained by immersion liquid absorption, which may influence the mechanical properties of denture base acrylic resins.…”
Section: Discussionsupporting
confidence: 93%
“…Specimens in the CNF-NB-A (0.05, 0.10, and 0.20 wt%) and CNF-NB-B (0.05 and 0.10 wt%) groups showed a significantly negative effect on flexural strength after immersion when compared with those in the other groups. This finding is consistent with the results of previous studies by Lee et al, where water or humid environment was reported to reduce the physical properties of some polymer resins 28,32) . The observation may be partially explained by immersion liquid absorption, which may influence the mechanical properties of denture base acrylic resins.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the present study, the specimens were stored in purified water at 37 °C for 50 h, following which the flexural test was performed in air. Some studies reported that the water immersion of denture base materials decreased their flexural strength and flexural modulus [ 42 ]. Therefore, when the flexural test is performed under water immersion according to ISO20795-1, the tendency of the flexural strength does not change, but the strength may decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The type of denture base resin affects the bonding ability of artificial teeth to denture base resins 12) . A previous report showed that the ultimate flexural strength of polycarbonate is higher than that of polyamide and polyester 24) . Further, the ultimate flexural strength of polyamide is lower than that of polycarbonate and polyester.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, polycarbonate is rigid and fairly inflexible, whereas polyamide is soft and highly flexible. The mechanical property of polyester is between that of polycarbonate and polyamide 24) . Furthermore, all specimens were soaked in water for 10 days in this study as it is possible for the mechanical properties to change because of water absorption.…”
Section: Discussionmentioning
confidence: 99%